Avaliação da atividade nitrificante da biomassa de um reator de lodos ativados - Vincoski, Geiciane Locatelli Alves (2025)
The removal of nutrients such as nitrogen and phosphorus is extremely important, as, as well as high concentrations of organic matter, these elements can cause various damages to aquatic fauna and flora. However, few effluent treatment systems are capable of eliminating these nutrients effectively. The activated sludge system stands out as one of the most efficient processes for removing nitrogen and phosphorus, in addition to presenting high treatment efficiency due to effluent recirculation. One of the variants of this system is the sequential batch reactor (RBS), in which the entire activated sludge process takes place in a single reservoir. The objective of this study was to evaluate the nitrifying activity of aerobic sludge from a sewage treatment plant located in southwestern Paraná. The sludge was maintained in a sequential batch reactor (RBS) with constant aeration, being fed with synthetic effluent every 48 hours over 76 days. During the experiment, variables such as temperature, pH and dissolved oxygen were monitored, and all remained stable throughout the period. Two respirometry tests were carried out to evaluate the sludge activity and the reaction speed to nitrogen consumption. The first test provided consistent data, while the second showed dispersion in results. The reaction speeds observed in both tests did not meet expectations due to the low activity of the sludge at the time of carrying out the tests.